Resolving Career Dilemmas: An Individual Assessment Approach to Career Planning - Ratna Devy Winayanti; Fendy Suhariadi; Ni Made Ayu Yuli Pratiwi; Ni Nyoman Imas Pradnyanita Wistarini; Putu Riana Artyanti Putri (Psikostudia : Jurnal Psikologi, 2025)
The management of capitation funds in the National Health Insurance (JKN) system required competent individuals to ensure transparency and financial accountability at primary healthcare facilities (FKTP). The JKN treasurer held a strategic role in planning, fund distribution, and reporting, making it necessary for the selection and assessment processes to be conducted comprehensively. This study aimed to evaluate the competencies of a JKN treasurer candidate based on analytical skills, planning, accuracy, communication, and work responsibility to ensure effective capitation fund management. The subject of this study was one treasured candidate, referred to by the initials AS. The research employed a multi-instrument assessment approach consisting of the Intelligence Structure Test (IST), DISC, Kraepelin, Papikostik, structured interviews, as well as the DAP (Draw-A-Person) test and Holland Self Inventory to understand the individual's personality traits and career interests. The results showed that the subject possessed strong intellectual potential and a personality profile compatible with administrative roles, based on Holland’s theory. However, aspects such as work responsibility and task planning still need improvement. The implications of this study emphasized the importance of an adaptive, competency-based assessment system and the need for continuous development programs. As a follow-up, a monitoring period of at least three months was conducted to observe the implementation of assessment recommendations and to ensure measurable improvements in the subject’s job performance. Pengelolaan dana kapitasi dalam sistem Jaminan Kesehatan Nasional (JKN) memerlukan individu yang kompeten untuk memastikan transparansi dan akuntabilitas keuangan di fasilitas kesehatan tingkat pertama (FKTP). Bendahara JKN memegang peran strategis dalam perencanaan, penyaluran, dan pelaporan dana, sehingga proses seleksi dan asesmen kompetensi harus dilakukan secara komprehensif. Penelitian ini bertujuan untuk mengevaluasi kompetensi calon Bendahara JKN berdasarkan aspek kemampuan analitis, perencanaan, ketelitian, komunikasi, dan tanggung jawab kerja guna memastikan efektivitas pengelolaan dana kapitasi. Subjek dalam penelitian ini adalah satu orang calon bendahara dengan inisial AS. Metode penelitian menggunakan pendekatan asesmen multi-instrumen yang terdiri dari Struktur Tes Intelijensi (IST), DISC, Kraepelin, Papikostik, wawancara terstruktur, serta tes DAP (Draw-A-Person) dan Holland Self Inventory yang digunakan untuk memahami aspek kepribadian dan minat kerja individu. Hasil penelitian menunjukkan bahwa subjek memiliki potensi intelektual yang baik serta kecenderungan kepribadian yang sesuai dengan karakteristik pekerjaan administratif berdasarkan teori Holland. Namun demikian, aspek tanggung jawab kerja dan perencanaan tugas masih perlu ditingkatkan. Implikasi dari penelitian ini menunjukkan pentingnya asesmen berbasis kompetensi yang adaptif serta perlunya program pengembangan berkelanjutan. Sebagai tindak lanjut, dilakukan pemantauan selama minimal tiga bulan untuk mengamati efektivitas implementasi rekomendasi asesmen dan memastikan peningkatan kinerja subjek secara nyata di lapangan.